Study of Genetic Variability, Path Analysis and Diversity of Selected Germplasm Lines of Wheat (Triticum aestivum L.), Under Very Late Sown Condition - P, Thakur; P, Upadhyay; K, Rashmi; Namrata; R, Prasad; K, Chandra; K, Madhukar; L. C., Prasad (International Journal of Bio-resource and Stress Management, 2018)
Fourteen diverse genotypes of wheat including three standard check variety were evaluated under heat stress condition during rabi season 2016-17 at Agriculture Farm, Institute of Agricultural Sciences, Banaras Hindu University. Genotypes were studied for genetic variability, path analysis and diversity with the aim to identify the superior genotype with significantly satisfactory yield under very late sown condition. The data were recorded for traits viz., days to heading, days to maturity, plant height, 1000 grain weight, grain yield plot-1 and biological yield plot-1. Analysis of variance showed significant differences for all the six traits. The grain yield plot-1 ranged from 2375–3600 g.The phenotypic coefficient of variation and genotypic coefficient of variation was observed highest for grain yield plot-1. Highest broad sense heritability was observed for 1000 grain weight while genetic advance was estimated to be highest for grain yield plot-1. Diversity analysis indicates that total 14 genotypes were grouped into 5 clusters. The highest inter-cluster distance was found between cluster IV and V followed by II and V. This exhibited that genotypes included in these clusters possess wide genetic diversity. Diversity study shows that the selection of genotypes for crosses from cluster V (WR544(C)) with cluster IV(PBW778), cluster II (HD3272) and cluster I (HI11621, WH1232, PBW757, DBW251, DBW250, HD3271 and WH1233) could give maximum heterosis and prove to be good recombinants. Hence, genotypes from such diverse groups can be selected for making the crosses and selection of desirable genotype for heat tolerance and better yield.